Proposta de construção de uma matriz insumo-produto para o Estado do Ceará a partir de dados dos contribuintes do ICMS para o ano de 2016 - Freire, Francisco Chagas Pordeus (2017)
This paper describes a proposed methodology for the construction of an input-output matrix for the state of Ceará based on the tax information of the ICMS taxpayers. It also presents the results obtained and also performs an analysis of the most significant sectors of the state economy, the level of relationship between sectors, the sectors most dependent on imports, sectors that export most. The data refer to the year 2016 and were collected from the computerized systems of the State of Ceará's Treasury Department, more specifically the ICMS Taxpayer Registration System, the Electronic Fiscal System - NFe, the Digital Tax Filing System - EFD and the Merchandise Transit Control System - SITRAM. From the data consolidated in the matrix, we find the predominance of the commerce sector as the most expressive for the economy of the state, followed by the manufacturing industry, being this sector the main one responsible for the flow of interstate commerce, as well as, for the exports. Keywords: